Impact of Ethical Leadership on Employee Performance in the Public Sector: Does Leader-Member Exchange Matter? - Kazeem Adebayo Oladimeji; Abdulrazaq Kayode Abdulkareem; Iyiola Tomilayo Akindele; Abdulhakeem Adejumo (Department of Public Administration, 2022)
This study assessed the impact of ethical leadership on employee performance in the public sector using leader-member exchange as a mediator. Data for this quantitative study was gathered using a structured questionnaire administered to Nigerian federal public officials in some selected ministries. A conceptual model was drawn and put to the test using the PLS-SEM. Based on the results, all hypotheses were significant at p < 0.001. More importantly, ethical leadership positively and significantly impacts leader-member exchange and employee productivity. More so, leader-member exchange mediates the relationship between ethical leadership and employee performance. This study’s findings improve on earlier studies on ethical leadership and leader-member exchange relationships. Also, it suggests the importance of leaders’ moral behaviour and their relationship with subordinates in the workplace, by imbibing workplace ethics. This study has added to the continuing discussion on ethical leadership and its implications in the public sector in a developing nation like Nigeria.